Pressure Vessels Structural Integrity Assessment Using Failure Analysis Diagrams (Brazilian Journal of Radiation Sciences (BJRS), 2025)
There is much discussion today about the possibility of extending the lifetime of industrial plant components due to economic factors. Pressure vessels are among the most expensive components, and their replacement can significantly impact the operation of an entire plant. In this context, several Fitness-for-Service (FFS) methodologies can be applied to assess structural integrity, addressing not only economic aspects but also enhancing safety. Failure Assessment Diagrams (FADs) are widely used in FFS methodologies to prevent future failures by analyzing crack-type defects. These diagrams establish acceptability criteria based on the material toughness ratio and loading ratio. Recommended practices utilizing the BS-7910, API-579, and R6 methodologies are addressed in this work, alongside principles from fracture mechanics, material properties, and solid mechanics. The main objective was to develop computer programs in Matlab to analyze a case study involving a pressure vessel manufactured from SA-516 Gr 70 steel, determining the critical dimensions of semi-elliptical cracks in longitudinal and circumferential orientations of a cylindrical section. Level 2 evaluation, the most commonly used in FFS methodologies, was applied to develop the programs. This study enabled the creation of tools to automate calculations and generate FAD graphs, considering the critical depth and length of cracks. These tools support decision-making in structural design requirements and provide a means of evaluating equipment in service with crack-type defects, extending its operational lifetime. The FFS methodologies studied are based on ASME Codes for pressure vessels and piping, particularly Sections III and XI. Based on the analysis of API-579, BS-7910, and R6 methodologies under the operating conditions of the case study, it is possible to conclude that, for normal evaluations, critical length (2c) = 40.64 mm and critical depth (a) = 10.16 mm are acceptable values. However, for evaluations requiring safety considerations under the R6 procedure, applicable to Class A service equipment in the nuclear sector, only critical length (l) = 5 mm and depth (a) = 2.5 mm are permissible values.